Model Tests on a Triple Screw Icebreaker (M5) for the United States Coast Guard. Part II - Icebreaking Tests - Dix, P. J. (1967)
A simple theory of bending with eventual tensile failure was assumed in scaling the thickness of ice which could be broken by the craft. A convenient material which could be sprayed into a large and uniform field was found to be modified model making wax. The wax mixture had ingredients which both reduced the strength of the material and limited the size of the fragments into which it broke during the icebreaking tests. See also Part 1, AD-861 590L.